Digital Information Security Policy in the National Security Strategy - Asmadi, Asmadi; Almutahar, Hasan; Sukamto, Sukamto; Zulkarnaen, Zulkarnaen; Listiani, Endang Indri; Sikwan, Agus (International Journal of Multidisciplinary Approach Research and Science, 2023)
Security comes from the Latin word secure, significantly different from the dangers, fears, and threats associated with traditional and non-traditional security methods. Meanwhile, defense is defined as the most vital technology for the state in carrying out its national security function. National security is defined as the dynamic state of a country which covers all aspects of the nation's life in facing threats. National security includes protection for the state, society, and individuals. Until now, experts have provided several different definitions of the terms security and defense. This article analyzes the current digital information security threats in national security strategies and the implementation of adequate legal protections. This article applies a descriptive qualitative research approach by conducting document analysis. This article describes various information security threats in Indonesia, including disinformation, privilege escalation, and protection against phishing threats, data forgery, and card crime. The similarities and differences between the concepts of defense and security can be observed through regulations, the terminology used, institutions, and constitutions. This article shows that national information security is closely related to policy and closely relates to security, especially ITE policies. It cannot be separated that the security situation of a country depends on security and defense but synergistically with other factors, namely economic, political, legal, socio-cultural, ideological, geographical, and demographic.